Dyadic discernment among young spouses in conflict: a decision science of marital and family therapy - Mohamed Nordin, Mohd Hamdan; Hassan, Siti Aishah; Ismail, Ismi Arif; Hamsan, Hanina H.; Abdul Aziz, Dzilal (Allied Business Academies, 2022)
Marital conflicts that strain young couples’ marriage typically go unresolved, leading to extended battles, physical injuries, third-party intervention, and, eventually, divorce. This study aims to define dyadic discernment as a decision science in the context of marital and family therapy. A couple who are in marital conflict with a wise and well-informed decision-making process is termed as dyadic discernment. Discernment counselling helps couples make wise and well-informed decisions on whether to (i) improve the marital relationship and increase marital satisfaction; (ii) divorce and work on individual well-being and custodial arrangements; or, (iii) maintain the status quo and cope with the current situation while waiting for a better time. Conflict issues and considerations in dyadic discernment among young spouses are discussed. Finally, the need for a psychometrically sound instrument called the Dyadic Discernment Scale (DDS) is presented in this study.